The Effects of Psychotherapist's and Clients' Interpersonal Behaviors during a First Simulated Session: A Lab Study Investigating Client Satisfaction - Moors, François; Zech, Emmanuelle (Frontiers in Psychology, 2017)
The purpose of this study was to examine the effects of psychotherapists’ behaviors during a first simulated therapy session on clients’ satisfaction, including their intention to pursue or drop out from therapy. The importance of psychotherapists’ warmth on clients’ satisfaction was examined to check previous findings stressing this determining factor. Examining the role of warm behaviors is however insufficient according to the interpersonal perspective. We therefore tested the role of the psychotherapist’s agentic behaviors since only a few studies provide contradictory results about the role of this interpersonal dimension on clients’ satisfaction and how it is influenced by matching up client and therapist’s profiles. To test our hypotheses and control for alternative therapy-related explanatory variables, we used different videos as experimental conditions manipulating the therapist’s behaviors. Seventy-five participants had to imagine themselves as potential clients arriving for a first therapy session. They successively watched a role-playing therapist behaving according to five randomized interpersonal profiles. Results confirmed that warmth was a major dimension predicting client satisfaction. They revealed that agency was also a determinant of client satisfaction and that its effects depended on the client’s own interpersonal agentic profile. Dominant clients were found to be more satisfied with the dominant psychotherapist than the submissive one while only submissive clients preferred the warm psychotherapist. These findings are discussed and suggest that therapists may need to be flexible and adapt their behaviors according to their client’s interpersonal profile to increase their client satisfaction and decrease drop outs.